2019
DOI: 10.1177/0042098019868377
|View full text |Cite
|
Sign up to set email alerts
|

School segregation in contemporary cities: Socio-spatial dynamics, institutional context and urban outcomes

Abstract: Social and social-spatial inequality are on the rise in the Global North. This has resulted in increasing segmentation between population groups with different social and ethnic backgrounds, and in differentiated access to cultural and material assets. With these changes, the relation between segregation in the educational sphere and segregation in the residential sphere has become crucial for understanding social reproduction and intergenerational social mobility. However, knowledge about this relation is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 39 publications
1
72
0
4
Order By: Relevance
“…Such a reform would ensure higher levels of proximity schooling, which would situate school segregation closer to residential segregation. Considering the relatively lower levels of residential segregation of southern European cities (Arbaci, 2019;Boterman et al, 2019) and the differences observed between residential and school segregation in our study, such a reform would most probably reduce spatial inequalities in education.…”
Section: Conclusion and Discussionmentioning
confidence: 69%
“…Such a reform would ensure higher levels of proximity schooling, which would situate school segregation closer to residential segregation. Considering the relatively lower levels of residential segregation of southern European cities (Arbaci, 2019;Boterman et al, 2019) and the differences observed between residential and school segregation in our study, such a reform would most probably reduce spatial inequalities in education.…”
Section: Conclusion and Discussionmentioning
confidence: 69%
“…These relative novelties open up, for example, the analysis of the relation between residential and school segregation. Recently, Boterman et al (2019) created an overview; they come to interesting conclusions about this relationship, for example that the relation between school segregation and residential segregation is not only strong, but also that the two aspects seem to reinforce one another. This has, unexpectedly, even been observed in 'extreme' contexts such as the Netherlands, in which residential segregation is firmly regulated and school choice is supposedly 'free'.…”
Section: Segregation In Other Domainsmentioning
confidence: 99%
“…Ultimately such policies would widen social gaps instead of diminishing them (Bridge, Butler, & Lees, 2011). Policies in the educational system promote inequality indirectly as well, both in the Netherlands and Europe (see a recent Urban Studies special issue on school segregation in contemporary cities (Boterman, Musterd, Pacchi, & Ranci, 2019)). Finally, structural path dependencies, such as the recent growth of larger citieslike Amsterdamhave a strong impact on spatial segregation patterns as well.…”
Section: Introductionmentioning
confidence: 99%